Validação de um questionário online de estresse em comunidade universitária. - RANGEL JUNIOR, Claro Luiz Antunes (2020)
Abstract: Objectives: assess the construct validity and reliability of an online questionnaire on stress - MAFIS. Methods: A sample composed of 116 individuals with an average age of 26.70 years, of these, 62.50% individuals were female, and 37.50% individuals were male, answered the Physical Activity and Health Map – MAFIS and PSS14. Were performed Spearman correlation analyzes, Cronbach’s Alpha reliability, Kaiser-Meyer-Olkin test (KMO) and Bartlett’s Sphericity. Results: Spearman’s correlation coefficient ranged from 0.10 to 0.60, and items with low correlation (How many times do you wake up or have your sleep been interrupted at night?), were maintained because sleep quality is directly linked to mood and evaluates other behaviors of interest to MAFIS, all markers have significance levels ≤ 0.05. The Cronbach coefficient obtained a value of α = 0.82, which is considered excellent. Exploratory analysis performed through the KMO test has shown a value of 0.82, with a significance level ≤ 0.05. The results of the MAFIS questionnaire were similar to other psychometric studies. Results: The MAFIS questionnaire is an adequate online tool that presents excellent reliability in the investigation of stress and the potential for stress change in university students.